Avaliação da política educacional de ampliação da jornada escolar: Programa Aprender Mais da rede municipal de ensino de Fortaleza-CE no período de 2019 a 2023 - Oliveira, Lidiana Gomes de (2023)
The various initiatives aimed at expanding students' length of stay in school institutions, under the premise of comprehensive student training, motivated the creation of public educational policies in the national, state and municipal contexts. In this sense, the research consisted of evaluating the public policy to extend the school day, developed in the city of Fortaleza through the Aprender Mais Program, from 2019 to 2023, formulated based on the discontinuity of the federal programs Mais Educação and Novo Mais Educação. The theoretical contribution was based on the reports of Anísio Teixeira, Darcy Ribeiro and John Dewey. Regarding the concepts of integral education, it is based by Paro (1988, 2009) and Guará (2006). The foundations for expanding the school day, from the perspective of full-time education, were based on Cavaliere (2004, 2007, 2014), Coelho (2009) and Moll (2009). In the field of public policy evaluation, the basis was sought in Arretche (2001), Gatti (2006, 2019) and Secchi (2020). Regarding educational policy, we used the works of Gadotti (1996) and Oliveira (2019). The research is qualitative in nature, based of In-Depth Assessment (Rodrigues, 2008, 2011). For this purpose, initially, an analysis of the official documents that materialize and regulate the aforementioned Programs was carried out, both at the federal and municipal levels. Data collection was carried out through the application of a questionnaire, consisting of open and closed questions and addressed to the managers of all Municipal Part-Time Schools. The analysis was carried out based on the assumptions of Discourse Analysis. The study sought to understand the breaks and permanence that existed between the predecessor federal programs and the Learn More Program, given the current Brazilian educational context. It is concluded that the increase in the length of stay of students in institutions with a focus on pedagogical actions has contributed to the protection of socially vulnerable students, since schools are called to take care and seek new paths that lead to the administration of social risks, guiding students in building their life project, making them aware of the causes and consequences of individual choices. It is also noted that comprehensive education on an extended day, implemented in municipal schools in Fortaleza, is a policy under construction, and is also characterized as a major challenge for educational managers, teachers and, consequently, for other segments. of school communities.